2017
DOI: 10.1001/jamapsychiatry.2017.1567
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in the Neurocircuitry of Obsessive-Compulsive Disorder

Abstract: To our knowledge, this is the first study demonstrating inflammation within the neurocircuitry of OCD. The regional distribution of elevated TSPO VT argues that the autoimmune/neuroinflammatory theories of OCD should extend beyond the basal ganglia to include the cortico-striato-thalamo-cortical circuit. Immunomodulatory therapies should be investigated in adult OCD, rather than solely childhood OCD, particularly in cases with prominent distress when preventing compulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 58 publications
3
86
0
Order By: Relevance
“…27,28 Ribonucleic acid transcriptomes from the basal ganglia of patients with Tourette syndrome demonstrate upregulation in immunerelated genes consistent with microglial activation, and neuroimaging studies demonstrate microglial activation in adults with OCD, and children with Tourette syndrome and paediatric autoimmune neuropsychiatric disorders associated with streptococcal infection. [29][30][31] However, these studies have limitations, and further studies are required to explore this hypothesis. 11 We acknowledge that the case series is selected and therefore open to bias, or coincidental association.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Ribonucleic acid transcriptomes from the basal ganglia of patients with Tourette syndrome demonstrate upregulation in immunerelated genes consistent with microglial activation, and neuroimaging studies demonstrate microglial activation in adults with OCD, and children with Tourette syndrome and paediatric autoimmune neuropsychiatric disorders associated with streptococcal infection. [29][30][31] However, these studies have limitations, and further studies are required to explore this hypothesis. 11 We acknowledge that the case series is selected and therefore open to bias, or coincidental association.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies showed the presence of inflammation in the cortico-striatal-thalamo-cortical circuit (Attwells et al, 2017) and the presence of greater plasma levels of IL-2, IL-4, IL-6, IL-10 and TNF-α levels in adult OCD patients compared to controls (Rao et al, 2015), as well as higher rates of anti-basal ganglia antibodies (Pearlman et al, 2014, Nicholson et al, 2012. Systemic autoimmune diseases are reported to be associated with an increased risk of OCD (Wang et al, 2018).…”
Section: Immunological Factors and Early Interventionmentioning
confidence: 99%
“…Evidence from human studies suggests that microglia are dysfunctional in at least a subset of individuals with neuropsychiatric disorders, as well as in neurodegenerative disorders such as Alzheimer's disease and chronic pain 17 . The range of neuropsychiatric disorders associated with at least some evidence of microglia dysfunction is broad and the list includes: Autism Spectrum Disorder (ASD), schizophrenia, bipolar disorder, major depression, OCD, and Tourette syndrome (TS) [17][18][19][20][21] . For example, postmortem studies of brain tissue from a small number of individuals with ASD have documented altered numbers of microglia in the dorsolateral prefrontal cortex [22][23][24] .…”
Section: Microglia and The Role Of The Immune System In Normal Brainmentioning
confidence: 99%